Easy Guide for Windows 3.1 - Goh, Ong Sing; Ong, L.L.; Tor, S.C. (Pustaka Timur Jaya, 1993)
This book is for everyone - if you've learned how to pul down the menus, but you're not interested in rewriting windows yourself, Easy Guide for Windows 3.1 will show you what you need to make Windows work for you.